PERCEIVED EXTERNAL PRESTIGE, DEVIANT WORKPLACE BEHAVIOR DAN JOB SATISFACTION PADA KARYAWAN INDUSTRI OTOMOTIF DI JAKARTA - Netania Emilisa; Dony Priandi Putra; Egabetha Amirah Yudhaputri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the effect of perceived external prestige to the workplace deviant behavior that is mediated by job satisfaction. The sample used in this study was 120 respondents who are employees in automotive industries in Jakarta of collected by purposive sampling method. Tests conducted by the method of Structural Equation Model (SEM). The results of this study are perceived external prestige has a positive influence on job satisfaction, but job satisfaction negatively affect the workplace deviant behavior. It can be concluded that job satisfaction has a negative influence in mediating the effects of perceived external prestige to the workplace deviant behavior.